Climate refugees in South Asia : protection under international legal standards and state practices in South Asia - Jolly, Stellina; Ahmad, Nafees (Singapore : Springer, 2019., 2019)
This book addresses the forms of legal protection extended to people displaced due to the consequences of climate change, and who have either become refugees by crossing international borders or are climatically displaced persons (CDPs) in their own homelands. It explores the legal response of the South Asian Jurisdictions to these refugee-like situations, and also to what extent these people are protected under current international law. The book critically examines and assesses whether States have obligations to protect people displaced by climate change under international refugee law (IRL) and international climate change law (ICCL). It discusses the issue of climate migration in South Asia, analyzes the legal and judicial response initiated by South Asian nations, and also investigates the role of SAARC in relation to climate change and climate refugees. Drawing on the International Legal Standards and States' Practices in South Asia regarding climate refugees, the book shows how IRL, ICCL, and IHRL (international human rights law) have been used to address and identify the gaps in the global legal protection framework concerning the contours of the normative debate on climate refugees, climate change displacement, migration, forced migration, susceptibility to climate change, typology of climate change-induced displacement, role of the SAARC and its municipal legal systems, approaches to climate change, human mobility and developing a hybrid regional law, or advocating a legal alternative of equal measure in a region characterized by diversity and multiculturalism. The book offers valuable takeaways for students, researchers, consultants, practitioners and policymakers alike.
Introduction -- Chapter 1-Conceptualizing the Climate Change Migration in South Asia -- Chapter 2-Climate Change Displacement and Refugees: 'Normative Debate' -- Chapter 3-Climate Change Migration: Legal Protection under International Refugee Law and Climate Change Legal Regime -- Chapter 4- Climate Refugees: South Asian States' Legal Protection Practices -- Chapter 5- Climate Refugees: The Role of South Asian Judiciaries in Protecting the Climate Refugees -- Chapter 6- The Role of the SAARC: Way Forward.
SOL
Book Finder International
Keywords: Climate change; Human rights; International environmental law; International humanitarian law; International Environmental Law; Climate Change/Climate Change Impacts; Human Rights; International Humanitarian Law, Law of Armed Conflict; Law